The evaluation of new marketing strategy of selected home appliances - Ghosh, Chinmoy (International research journal of management, IT and social sciences, 2016)
The struggle for existence and growth is indeed very hard for firms in a competitive environment. As the environment changes their vision and objectives, structure, a portfolio of business, market and competitive strategies Poke Strategy, includes the four ingredients such as Price, offers, brand, competitive marketing strategies.